Sistem Informasi Pertanian Berbasis Kecerdasan Buatan (E-Tandur) - Nina Amalia; Oscar Rachman; Roni Surahman (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2020)
The topic of this research is the design of a model of agricultural information systems based on (IOT) or the Internet of Things that is used as a medium to improve the precision of the quality of agricultural products. For the compiler of this information system data is in the form of tabular data and spatial data. Tabular data in the form of numerical data from land, plant, and water availability data. Spatial data contains area data, position of agricultural land. The method used in the analysis in this study is Farming System Analysis (FSA) and approach system method used is object oriented. The purpose of this study is based on the frequent changes in the level of harvest feasibility in the agricultural sector, where the current level of yield feasibility does not only occur on unproductive land but also encroaches on land with good productivity. It is necessary to provide an information system that can support the observation of the feasibility of the yields to be produced by the agricultural sector. By integrating this system into the agricultural sector, it will result in increasing the quality, quantity, resilience and cost effectiveness of agricultural production, and shifting the paradigm of application from Object Oriented to Smart Object Oriented based on the Internet of Things (IoT).